Enhanced therapeutic effect on colitis with powder formulations of Painong San associated with the promotion of intestinal adhesion and absorption. (10th May 2022) - Li, Jiacheng; Rui, Xuelin; Xu, Li; Liu, Yang; Yang, Ye; Yin, Dengke
Abstract: Ethnopharmacological relevance: Painong San is a prescription composed of traditional Chinese medicine, which has been used to treat colitis. The Painong San's usage recorded in "Jingui Yaolve" by Zhongjing Zhang in the Later Han Dynasty is powder. However, the decoction is often used in reality. It's unclear which dosage form of Painong San is more suitable for colitis treatment and why? Aim of the study: This study aims to evaluate the different therapeutic effects of Painong San (a powder of Painong San) and Painong Decoction (a decoction of Painong San) on a dextran sulfate sodium salt-induced colitis model and the possible reasons of these different effects. Materials and methods: The contents of paeoniflorin, naringin, heperidin and neohesperidin in Painong San and Painong decoction were determined by an ultra-performance liquid chromatography system. The therapeutic effect on colitis was evaluated by intragastric administration of Painong San or Painong Decoction in dextran sulfate sodium salt-induced mouse model. The accumulated release rate of Painong San in vitro was analyzed with artificial gastric juice, artificial intestinal juice, and artificial colon juice. The concentrations of four compounds in the blood, intestinal contents, and intestinal fluids were detected by an-ultra performance liquid chromatography-tandem quadrupole mass spectrometry system. In situ intestinal perfusion experiments were used to observe the adhesion of Painong San to the intestine's surface. The expression of Mucin-2 and Trefoil Factor 3 in the colon was studied by immunohistochemistry. Results: There was no significant difference in the contents of the four compounds in Painong San and Painong Decoction. In vivo, Painong San has a better therapeutic effect than Painong Decoction in the treatment of colitis. Painong San could be released slowly in the simulated human digestion environment in vitro, and more Painong San particles were released on the intestinal surface in the colitis state in the healthy state. Painong San could increase the bioavailability of hesperidin and neohesperidin, and their concentrations in local intestinal tissue, intestinal fluid and intestinal contents. The expression of trefoil Factor 3 protein on the surface of the colon tended to be in the intestinal cavity and overlapped with the expression of mucin-2. Trefoil Factor 3 accumulates in the intestinal cavity of the colon in the state of colitis, which may increase the adhesion of Painong San particles. Conclusion: In conclusion, this experiment proved that Painong San is a more suitable dosage form for the treatment of dextran sulfate sodium salt-induced colitis than Painong Decoction, which may be related to the enhancement of Painong San particle adhesion to the intestine in colitis. This study provides a reference for the selection of clinical dosage forms for traditional Chinese medicine. Graphical abstract: Image 1